The Influence of Fear of Missing Out (FoMO) on Consumer Behavior in Teenagers Using the Shopee Application in Jakarta - Marisa Santoso, Elsa (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to analyze the impact of Fear of Missing Out (FoMO) on consumer behavior among adolescent Shopee users in Jakarta. Shopee, as a popular e-commerce platform in Indonesia, has influenced consumption patterns, especially among female students, through attractive promotions such as discounts and free shipping. FoMO, which is the fear of missing out on popular opportunities or trends, can drive individuals to make impulsive purchases, even when these purchases do not meet their basic needs. This research employs a quantitative method using FoMO and consumer behavior measurement tools that have been validated. The results of the analysis indicate that FoMO has a positive influence on consumer behavior, with an influence rate of 59.6%. These findings suggest that higher levels of FoMO are associated with a greater likelihood of engaging in consumptive behavior, such as buying items merely to avoid missing out on discounts. This study reinforces the understanding that psychological factors such as FoMO can influence irrational purchasing decisions among adolescent e-commerce users.